PENGARUH BRAND DESTINATION BERBASIS TRI HITA KARANA TERHADAP WORD OF MOUTH DAN NIAT BERKUNJUNG KEMBALI WISATAWAN KE NUSA PENIDA - Vena Swara, Ni Nyoman Adityarini Abiyoga; Abiyoga Wulandari, Ni Luh Adisti; Wimba, I Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.11.TAHUN 2020DO - 10.24843/EEB.2020.v09.i11.p03, 2020)
The purpose of this study was to analyze the effect of brand destination based on Tri Hita Karana to word of mouth and intention to revisit Nusa Penida tourist destination. The research used descriptive and quantitative analysis with a total sample size of 100 tourists, both domestic and foreign who had visited Nusa Penida. The results of the study stated that brand destination based on Tri Hita Karana had a positive and significant effect on word of mouth and and intention to revisit Nusa Penida tourist destination. It is recommended that tourism development in Nusa Penida be carried out by collaborating traditional values, social, cultural, and local wisdom of the community while maintaining harmonization of God, human and environmental relations as the Tri Hita Karana philosophy